2014
DOI: 10.1016/j.cej.2014.06.102
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of a Cu-based oxygen carrier: Relevance of temperature and oxygen partial pressure on reduction and oxidation reactions rates in Chemical Looping with Oxygen Uncoupling (CLOU)

Abstract: The kinetic of reduction of CuO to Cu 2 O with N 2 +O 2 mixtures and the oxidation of Cu 2 O to CuO with O 2 of a Cu-based oxygen carrier for the CLOU process has been determined in a TGA. For kinetic determination, the O 2 concentrations were varied between 0 and 9 vol.% for reduction, and between 21 and 1.5 vol.% for oxidation reactions; temperature was varied between 1148 and 1273 K for the reduction and between 1123 and 1273 K for the oxidation. The oxygen carrier showed high reactivity 2 both in oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 31 publications
(88 reference statements)
4
59
0
1
Order By: Relevance
“…6.A. Thus, re-oxidation of CuAlO 2 formed during reduction was not allowed, which was also observed by others in previous works [17,44] [31]. Considering the incomplete decomposition and oxidation of the CuAl 2 O 4 , the effective oxygen transport capacity was R OC,CLOU =2.2 wt.%, which means that only the first 40 seconds in Fig.…”
Section: Cycles Alternating N 2 and Airsupporting
confidence: 70%
See 1 more Smart Citation
“…6.A. Thus, re-oxidation of CuAlO 2 formed during reduction was not allowed, which was also observed by others in previous works [17,44] [31]. Considering the incomplete decomposition and oxidation of the CuAl 2 O 4 , the effective oxygen transport capacity was R OC,CLOU =2.2 wt.%, which means that only the first 40 seconds in Fig.…”
Section: Cycles Alternating N 2 and Airsupporting
confidence: 70%
“…The results suggested that the solids inventory in the fuel reactor could be higher than 600 kg/MW th to reach CO 2 capture higher than 95% for the lignite combustion [31]. Thus, an excess of oxygen would be expected in gas stream from fuel reactor, if both high CO 2 capture and complete fuel combustion was desired.…”
Section: Introductionmentioning
confidence: 99%
“…CLOU is considered a promising technology to burn solid fuels with CO2 capture [14]. Oxygen release from oxygen carriers, coal pyrolysis, and char/syngas combustion all take place in the fuel reactor (Reactions 3, 6-8) [46]. Three of the major metal oxide systems identified for CLOU are CuO/Cu2O, Mn2O3/Mn3O4, and Co3O4/CoO [14].…”
Section: Major Proposed Solid Fuel Chemical-looping Combustion Processesmentioning
confidence: 99%
“…The impregnated carrier may have a slightly higher degree of dispersion of the active phase than the physically mixed carrier. Adábez-Rubio et al studied the kinetics of Cu-based oxygen carriers (Cu60MgAl) for CLOU using TGA [46]. The reduction of CuO to Cu2O was done under a mixture of N2 + O2 and the oxidation of Cu2O to CuO was done under O2.…”
Section: Kinetic Studies Of Oxygen Carriers and Solid Fuels Using Tgamentioning
confidence: 99%
See 1 more Smart Citation